Source rock evaluation for hydrocarbon generation in Halal oilfield, southern - Mohamed M. El Nady; Naglaa S. Mohamed (Egyptian Journal of Petroleum)
The aim of this paper is to define the source rock potential of hydrocarbon generation through the determination of: (1) the quantity of organic matter, (2) present day kerogen types, (3) thermal maturity and (4) source organic matter input and depositional conditions of the source rock from Kareem, Rudeis and Matulla Formations, and Nubia Sandstone in 2 wells namely GH 376-1 and GH 404-1 throughout pyrolysis, vitrinite reflectance measurements and gas chromatographic analyses. The results suggest that Kareem and Rudeis source rocks have poor to good generating potential to generate both gas and oil at optimum maturity, Matulla source has a very good while Nubia has poor generating potential to generate both oil and gas at optimum maturity. The organic matter of Kareem, Rudeis and Nubia source rocks was deposited in marine environment under reducing conditions, while Matulla Formation deposited in transition environments and tends to be of terrestrial rather than marine sources.